Choreonarratives : Dancing Stories in Greek and Roman Antiquity and Beyond - Gianvittorio-Ungar, Laura; Schlapbach, Karin (Mnemosyne Supplements Online, Supplement 2020, ISBN: 9789004419193., 2021)
Choreonarratives , a collection of essays by classicists, dance scholars, and dance practitioners, explores the uses of dance as a narrative medium. Case studies from Greek and Roman antiquity illustrate how dance contributed to narrative repertoires in their multimodal manifestations, while discussions of modern and contemporary dance shed light on practices, discourses, and ancient legacies regarding the art of dancing stories. Benefitting from the crossover of different disciplinary, historical, and artistic perspectives, the volume looks beyond current narratological trends and investigates the manifold ways in which dance can acquire meaning, disclose storyworlds ranging from myths to individual life-stories, elicit the narratees' responses, and generate powerful narratives of its own. Together, the eclectic approaches of Choreonarratives>/i> rethink dance's capacity to tell, enrich, and inspire stories. Contributors are Sophie M. Bocksberger, Iris J. Bührle, Marie-Louise Crawley, Samuel N. Dorf, Karin Fenböck, Susan L. Foster, Laura Gianvittorio-Ungar, Sarah Olsen, Lucia Ruprecht, Karin Schlapbach, Danuta Shanzer, Christina Thurner, Yana Zarifi-Sistovari, Bernhard Zimmermann.